Seborrheic Dermatitis: A Contemporary View of Pathogenesis, Diagnosis and Treatment – A Narrative Review of the Current Literature - Panek, Gabriela; Kość, Kacper; Muzyka, Natalia; Prusek, Adam; Giersz, Jakub; Rumin, Magdalena; Piliński, Remigiusz; Gosztyła, Dominika; Abramowicz, Amanda; Bukwald, Weronika (Quality in Sport, 2026)
Background. Seborrheic dermatitis (SD) is a common, chronic, relapsing inflammatory dermatosis affecting sebum-rich areas, primarily the scalp, face, and intertriginous regions. Despite its generally benign nature, the relapsing course, visible distribution of lesions, and pruritus may substantially reduce patients’ quality of life. Methods. A targeted literature review was conducted in the PubMed and Cochrane Library databases. Systematic reviews, meta-analyses, randomized clinical trials, and up-to-date narrative reviews on seborrheic dermatitis were included. The search terms comprised: “seborrheic dermatitis”, “Malassezia”, “topical treatment”, “anti-inflammatory treatment”, and “maintenance therapy”. Results. Available evidence supports a multifactorial pathogenesis of SD, involving Malassezia yeasts, epidermal barrier dysfunction, and an abnormal host immune response. Topical antifungals remain the cornerstone of treatment, while short courses of anti-inflammatory therapy are effective during flares. Increasing emphasis is placed on maintenance strategies and steroid-sparing approaches. New nonsteroidal anti-inflammatory agents show promising efficacy and safety. Conclusions. Long-term control of seborrheic dermatitis is best achieved through a stepwise therapeutic approach aimed at rapid management of flares and maintenance strategies that reduce relapse frequency